A new numerical model for polymer-confined rectangular concrete columns. Issue 7 (8th January 2018) - Isleem, Haytham F.; Wang, Daiyu; Wang, Zhenyu
Abstract : A new numerical model to estimate the strength of unreinforced and reinforced concrete columns of rectangular cross-section confined with fibre-reinforced polymer wraps is introduced. The model is based on data from 456 tests compiled from 30 studies available in the technical literature. The test database covers unconfined concrete strengths varying from approximately 10 to 80 MPa and the width and depth of the cross-sections ranged between 90 and 500 mm. The effects of aspect ratio and size of the cross-section, effective rupture strain of the polymer, corner radius and internal hoop steel reinforcement are all accounted for in the model. Based on the test database, thresholds of lightly and heavily confined concrete are proposed to ensure that columns have a sufficient level of polymer confinement. Model predictions were found to be in good agreement with the test results.